The Mosquito Coast - Weir, Peter, 1944-; Schrader, Paul, 1946-; Ford, Harrison, 1942-; Mirren, Helen; Phoenix, River; Theroux, Paul; LC Purchase Collection (Library of Congress); Copyright Collection (Library of Congress) (United States : Warner Bros. Pictures, United States : Warner Home Video, 1986)
An inventor, disillusioned by an America that "buys junk, sells junk, eats junk" and is always poised on the brink of nuclear disaster, uproots his family to build a utopia in the jungle of Central America.
Copyright: The Saul Zaentz Company. DCR 1986; PUB 21Nov86; REG 13Mar87; PA318-225.
Copyright notice on videodisc jacket: Warner Home Video ; 1987 (for package design & summary).
Videodisc is reissue copy; reissue date from copyright date on videodisc jacket.
Two discs in one jacket.
Part of summary from videodisc jacket.
On videodisc jacket: 11711 A/B.
Keywords: Utopian plays; Inventors -- Drama; Genius and mental illness -- Drama; Self-destructive behavior -- Drama; Families -- Drama; Mosquitia (Nicaragua and Honduras) -- Drama; Features; Sociological films and programs; Videodiscs